The Agrarian Reform of the Fifties in Calabria. Knowledge, Conservation and Transformation of the Landscape of the Marquisate of Crotone - Maria Rossana Caniglia; Francesca Passalacqua (ArcHistoR Architettura Storia Restauro: Architecture History Restoration, 2020)
The Sila law (12/05/1950), first act of that land innovation so much invoked in the years after the Second World War to respond to the backwardness of the agrarian system, officially initiated Agricultural Reform in Calabria. The Institution of the “Opera for the Valorizzazione on the Sila (OVS) built the settlement system in the Silano-Jonico District, at the same time as infrastructure works and the assignment of farms: small rural towns and farmhouses.